In memory of academician NAS RK, doctor of physical and mathematical sciences, professor Shamshi Sharipovich Sarsembinov - board, Editorial (Recent Contributions to Physics, 2012)
Academician Sh.Sh. Sarsembinov founded a new scientific direction in the physics of semiconductors: control of the electronic properties of semiconductors with a non-crystalline structure and together with the students developed the physical basis for modifying the electronic properties of non-crystalline semiconductors.